2014
DOI: 10.1152/jn.00383.2014
|View full text |Cite
|
Sign up to set email alerts
|

Hypersynchrony despite pathologically reduced beta oscillations in patients with Parkinson's disease: a pharmaco-magnetoencephalography study

Abstract: Parkinson's disease (PD) is a progressive debilitating neurodegenerative disorder clinically manifest by motor, posture and gait abnormalities. Human neurophysiological studies recording local field potentials within the subthalamic nucleus and scalp-based electroencephalography have shown pathological beta synchrony throughout the basal ganglia-thalamic-cortical motor network in PD. Notably, suppression of this pathological beta synchrony by dopamine replacement therapy or deep-brain stimulation has been asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
99
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 76 publications
(108 citation statements)
references
References 44 publications
3
99
4
Order By: Relevance
“…107 Recent work from our laboratory confirmed that un-medicated patients with PD have pathologically high synchrony between the primary motor cortices, and further showed that these patients have significantly diminished beta amplitude relative to demographically-matched controls during the resting-state. 112 Interestingly, administration of dopaminergic medication selectively ameliorated these differences in beta amplitude. 112 …”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
See 1 more Smart Citation
“…107 Recent work from our laboratory confirmed that un-medicated patients with PD have pathologically high synchrony between the primary motor cortices, and further showed that these patients have significantly diminished beta amplitude relative to demographically-matched controls during the resting-state. 112 Interestingly, administration of dopaminergic medication selectively ameliorated these differences in beta amplitude. 112 …”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…112 Interestingly, administration of dopaminergic medication selectively ameliorated these differences in beta amplitude. 112 …”
Section: Parkinson's Disease (Pd)mentioning
confidence: 99%
“…Further, a multitude of studies examining the neurophysiology of movement disorders, such as Parkinson’s disease (Brown, 2007; Cassidy et al, 2002; Heinrichs-Graham et al, 2014a; Heinrichs-Graham et al, 2014b; Little and Brown, 2014; Pollok et al, 2012; Weinberger et al, 2006), cerebral palsy (Kurz et al, 2014), Tourette syndrome (Franzkowiak et al, 2010; Niccolai et al, 2015; Tinaz et al, 2014), dystonia (Hinkley et al, 2012), and stroke (Rossiter et al, 2014a; Shiner et al, 2015; Wilson et al, 2011a) have shown aberrant sensorimotor beta power at rest and/or during movement. These beta aberrations are often correlated with symptom severity, which suggests that the degree of motor impairment is closely tied to beta activity in the motor cortices.…”
Section: Introductionmentioning
confidence: 99%
“…Local beta oscillations and their coordination between regions are implicated in numerous functions, including sensory perception, selective attention, and motor planning and initiation (2,3,6,7,9,(11)(12)(13)(14)(15). Neocortical beta oscillations are disrupted in various neuropathologies, most notably Parkinson's disease (PD), in which treatments that alleviate motor symptoms also reverse the neocortical beta disruption (16,17). Although associations between beta and performance suggest a crucial role in brain function, beta rhythmicity might not be important per se but instead may be an epiphenomenal consequence of other important processes.…”
mentioning
confidence: 99%
“…These findings make several predictions about optimal states for perceptual and motor performance and guide causal interventions to modulate beta for optimal function. beta rhythm | magnetoencephalography | computational modeling | sensorimotor processing | Parkinson's disease B eta band rhythms (15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) are a commonly observed activity pattern in the brain. They are found with magnetoencephalography (MEG) (1)(2)(3)(4), EEG (5,6), and local field potential (LFP) recordings from neocortex (7)(8)(9) and are preserved across species (10).…”
mentioning
confidence: 99%